Acute presentation of ruptured ovarian cyst secondary to torsion with ipsislateral concomitant ectopic pregnancy: A case report - Pandey, Mahendra R; Ojha, Neeva (Nepal Journal of Obstetrics and Gynaecology, 2014)
Twenty-one year unmarried regularly menstruating lady without history of amenorrhea presented with acute abdomen in TU Teaching Hospital –Emergency Department. On evaluation urine pregnancy test was positive. Urgent ultrasound revealed multiloculated cystic lesion measuring 8.5 x 8 x 6.7 cms in the right adnexa anterolateral to the uterus with no intrauterine gestational sac. She underwent emergency laparotomy with right salpingo-oophorectomy. On laparotomy there was twisted and ruptured right ovarian cyst with unruptured ampullary pregnancy on the same side. There was coexistence of these two conditions which presented as acute abdomen. DOI: http://dx.doi.org/10.3126/njog.v3i2.10834 Nepal Journal of Obstetrics and Gynaecology Vol.3(2) 2008; 54-56